Contractual Fairness in Internasional Trade an Analysis of Business Law Standards - Putu Laksmi Noviyana; Dewa Gede Pradnya Yustiawan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Contractual fairness is a fundamental principle in international trade, ensuring balanced and equitable agreements between parties of different jurisdictions. However, disparities in bargaining power, varying legal standards, and cultural differences often lead to imbalances that challenge the notion of fairness. This study examines the concept of contractual fairness within the framework of international trade and analyzes the business law standards that govern cross-border agreements. The research explores how contractual fairness is interpreted and enforced under different legal systems, emphasizing its significance in promoting transparency and fostering trust in international business relationships. Through a comparative analysis of legal frameworks in major trading jurisdictions, the study identifies key factors that influence fairness, including standardized contractual terms, dispute resolution mechanisms, and the role of international organizations like the United Nations Commission on International Trade Law (UNCITRAL). This study also highlights the challenges of achieving fairness in complex trade agreements, such as those involving developing economies, where unequal access to legal resources and expertise can create significant disadvantages. By addressing these challenges, the research aims to propose practical solutions for harmonizing business law standards and enhancing contractual fairness in international trade.The findings of this study are expected to contribute to the ongoing dialogue on global trade reform, offering insights for policymakers, legal practitioners, and businesses. The paper concludes by emphasizing the need for a balanced approach that ensures fairness while maintaining the flexibility necessary for dynamic international trade practices.